Fast Intra prediction algorithm for quality scalable video coding. Issue 4 (April 2016) - Wang, Dayong; Sun, Yu; Bai, Mingze; Li, Hongjian; Yuan, Chun; Huang, Yuanyuan
Abstract The coding efficiency of currently scalable video coding is very high at the cost of high coding complexity. Therefore, it is extremely important to improve the coding speed. By making use of the advantage of the quality scalable video coding (QSVC) structure, we propose a new fast Intra coding algorithm for QSVC. Based on the coding structure of QSVC, temporal, spatial and inter-layer correlations are employed together to predict candidate macro-block (MB) modes and their encoding orders to exclude low possible modes, and then three new early termination methods are proposed. In addition to MB modes, temporal, spatial and inter-layer correlations are also adopted together to estimate weight values and orders of all directional modes. Experimental results demonstrate that the coding speed of the proposed algorithm can be improved by 63.58 % in average with negligible coding loss.